Investigating the Pedagogical Values of Smartphones: Students’ Experiences from Nepal’s Rural Community Schools - Kandel, Sunita; Khanal, Govinda Prasad (Journal of NELTA Gandaki, 2024)
The utility of smartphones for school-age learners has become much discussed and debated issue recently. Teachers, school administrators and students have their personal beliefs about the pedagogical value of smartphones. This paper aims to explore secondary-level students’ lived experience of using smartphones to support content and language learning. It examines socio-psychological pressures experienced by learners in using smartphones, particularly in schools. This qualitative phenomenological study was conducted among sixteen rural secondary students (Grade 12) in the Central-Western Tarai in Nepal. The findings indicated the perceived pedagogical value of smartphones as the students could enhance self-learning when they were provided with proper guidance and support from their teachers. Although students experienced pressure from parents and teachers to avoid smartphone use, they found alternative ways of using them to support their learning. The findings implied that the students’ increased access to technology can support enhancing the learning of the curricular contents and language.